Tahap Kecenderungan Minat Pelajar Usim Terhadap Kursus Titas - Latifah Abdul Latiff; Ros Aiza Mohd Mokhtar; Khadijah Muda; Abd Hakim Mohad @ Mohamad Ramli (Penerbit UTM Press, Universiti Teknologi Malaysia, 2024)
Indexed by MyCite